PENGARUH ETIKA BISNIS ISLAM TERHADAP KEPUASAN KONSUMEN PADA USAHA AYAM POTONG MUJUR DI DESA SIKARA-KARA 1 KECAMATAN NATALKABUPATEN MANDAILING NATAL - Maulana Maulana; Arwin Arwin; Sari Fitri (BORJUIS: JURNAL OF ECONOMY, 2024)
This research aims to determine the influence of Islamic business ethics on consumer satisfaction in the Mujur broiler chicken business. This research was carried out at the Mujur broiler chicken business in Sikara-Kara 1 Village, Natal District, Mandailing Natal Regency. This research method used is quantitative by describing the data using numbers. Sampling was carried out using purposive sampling technique. The sample of this research was 100 people using a quantitative approach. Data analysis using the t test obtained a calculated t result of 5.310 and a t table at the 5% significance level of 1.664, so t calculated > t table. This shows that there is an influence of Islamic business ethics on consumer satisfaction in the Mujur broiler business in Sikara-Kara 1 Village, Natal District, Mandailing Natal Regency.